2021
DOI: 10.1155/2021/5547044
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influencing Factors of Mobile Digital Music Selection in Subhealthy People Based on Perceived Value Theory

Abstract: Background. The mode of combining mobile terminals and mobile digital music has gradually entered a bottleneck period while promoting the development of the mobile terminal industry. Proposing personalized solutions for specific groups of people including subhealthy people has become the current direction for the further long-term development of this mode. Understanding the influencing factors that affect subhealthy people’s selection of mobile digital music is an urgent problem that needs to be solved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…But in this study, zakat literacy does not affect the perceived value or the value that can be felt from the results of this study. In line with research (Jiang et al, 2021) It is believed that the social environment has a great influence on our intention or motivation to pay Zakat. This motivation arises from the individual's response to the dominant behaviour in an environment.…”
Section: E Coefficient Of Determination (R2)supporting
confidence: 60%
“…But in this study, zakat literacy does not affect the perceived value or the value that can be felt from the results of this study. In line with research (Jiang et al, 2021) It is believed that the social environment has a great influence on our intention or motivation to pay Zakat. This motivation arises from the individual's response to the dominant behaviour in an environment.…”
Section: E Coefficient Of Determination (R2)supporting
confidence: 60%
“…In formula (5), δ is the number of training set data. e essence of RBM is to map the original data to different feature spaces to retain the key feature information of the data and obtain a better low-dimensional representation.…”
Section: Deep Belief Network Andmentioning
confidence: 99%
“…e essence of RBM is to map the original data to different feature spaces to retain the key feature information of the data and obtain a better low-dimensional representation. According to this idea, an idea of optimizing RBM training in this paper is to replace the objective function formula (5) of RBM equally. If the output of each RBM is converted according to formula (6), the output of its hidden layer can be inversely converted and then compared with the original data.…”
Section: Deep Belief Network Andmentioning
confidence: 99%
See 1 more Smart Citation
“…PV has been broadly utilized in relevant research in the domain of Consumer's purchase/buying intention and PV. Abundant research revealed that PV is a better predictor as compared to quality or satisfaction for predicting the buying/purchase intentions of the consumer (Jiang et al, 2021).…”
Section: Consumer Perceived Value (Cpv)mentioning
confidence: 99%